Diseño y simulación de un prototipo de máquina tostadora de cacao con capacidad de carga de 10 kg (2021)
This project aims to: design an optimal prototype of a machine cocoa roaster with load capacity of 10kg 3D design and modeling of the prototype done by using a tool CAD: 3D SOLIDWORK; the realization of electrical drawings: EPLAN ELECTRIC; the programming software and simulator logic: PLC LOGO SOFT V8.0; software for screen design and simulation HMI that interacts with the system: SCADA INTOUCH. Obtaining the structural design and final mechanic of an Industrial Toaster Electric with the ability to perform a toast approximately 10 Kg per patch of cocoa, electrical diagrams will be made, implementing logic programming sequentially, calculating the costs for the execution of the functional product, adapted to the needs and improvements requested by the Username.